Study on the Influence of Clay Content on the Freeze–Thaw Characteristics and Mechanisms of Solidified Low-Liquid-Limit Clay - Ruifan Lu; Junjie Yang; Yalei Wu (Applied Sciences, 2025)
This study investigates the effects of clay content on the strength and microstructural mechanisms of artificially prepared low-liquid-limit clay solidified with SSGM binder, composed of salt sludge (SAS), steel slag (SS), ground granulated blast-furnace slag (GGBS), and light magnesium oxide (MgO), and the law of influence of viscous particles content on the strength of the solidified low-liquid-limit clay and its microscopic mechanism were investigated through a freeze–thaw cycle test and microscopic test. The results indicate that, under freeze–thaw cycles, both the mass and unconfined compressive strength of the solidified soil decrease with increasing cycle number. At the same number of cycles, samples with lower clay content exhibit smaller mass loss rates and unconfined compressive strength loss rates. Microstructural tests reveal that the hydration products of the binder, including C-S-H, C-A-S-H, C-A-H, and AFt, not only cement soil particles and fill internal pores but also interconnect to form a mesh-like structure, enhancing internal stability. However, as freeze–thaw cycles progress, the structure of the solidified soil deteriorates, with an increase in large pores and the formation of penetrating cracks and voids, leading to reduced strength. The SSGM binder demonstrates excellent freeze–thaw resistance for solidifying low-liquid-limit clay and improves the utilization rate of industrial waste, showing promising application potential in permafrost regions.